Development of a fully automated high throughput PCR for the detection of SARS-CoV-2: The need for speed. Issue 1 (1st January 2020) - Mayer, Florian J.; Ratzinger, Franz; Schmidt, Ralf L.J.; Greiner, Georg; Landt, Olfert; Am Ende, Alexander; Corman, Victor M.; Perkmann-Nagele, Nicole; Watkins-Riedel, Thomas; Petermann, Dagmar; Abadir, Karoline; Zweimüller-Mayer, Josef; et al.
ABSTRACT: Currently, testing for coronavirus is performed with time and personnel consuming PCR assays. The aim of this study was to evaluate the sensitivity, specificity and capacity of a fully automated, random access high-throughput real-time PCR-based diagnostic platform for the detection of SARS-CoV-2. The NeuMoDx N96 system displayed an equal or better detection rate for SARS-CoV-2 compared with the LightCycler 480II system and showed a specificity of 100%. The median PCR run time for all 28 PCR runs was 91 (IQR 84–97) minutes. The capacity of the NeuMoDx N96 could easily surpass the capacity of most currently used molecular test systems and significantly reduce the turn-around time.